T cells development in vitro : a minimalist approach - Lapenna, Antonio (Cranfield University, 2012)
T lymphocytes are considered an essential and advanced component of the immune system, since these cells are able to discriminate self from non-self, start up an immune reaction and further develop into memory cells. However, therapies based on the use of patient derived newly generated T cells reinoculated into humans do not exist. This is due to difficulties in replicating the peculiar conditions required for T cell development in vitro. The systems developed so far are based on the use of animal or unrelated human thymic tissue and therefore they would not be adequate to be used in any clinical application. Having conjectured that human skin cells, rearranged in a threedimensional fashion, would be able to support the development of human T lymphocytes from hematopoietic stem cells, we developed a model consisting of human skin keratinocytes and fibroblasts arrayed on a synthetic matrix so to create a prototype suitable to be translated into the clinic. In this way we were able to induce few hundred cord blood CD34⁺ haematopoietic stem cells to entirely develop into mature CD4⁺ or CD8⁺ T lymphocytes in vitro. However, circulating adult peripheral CD34⁺ precursors failed to survive in the same conditions. Finally we were able to explain our success as consequence of strong induction of the Notch delta ligand Dll-4 by the keratinocytes cultured in the construct. In synthesis, we report here for the first time that skin keratinocytes, in the presence of fibroblasts and reconfigured in a three-dimensional arrangement, are able to induce the differentiation of a minimal amount of cord but not adult blood stem cells into fully differentiated T cells by acting through the Dll-4 Notch signaling pathway in vitro.
Keywords: T cell development; Notch signalling; Dll-4; HSC; stem cells ageing